The implementation of fiscal decentralization in accordance with Law No 32/2004 regarding local government and No. 33/2004 regarding inter-government fiscal relationship was considered as the new era management and local government budget. The objectives of this study were (1) to identify factors affecting regional fiscal, regional economy, poverty ond food security and (2) to evaluate impact of fiscal decentralization policy on poverty and food security in West Java. The descriptive analysis - Wiwiek Rindayati; Bunasor Sanim; M. Parulian Hutagaol; Hermanto Siregar (Forum Pasca Sarjana, 2008)
The implementation of fiscal decentralization in accordance with Law No 32/2004 regarding local government and No. 33/2004 regarding inter-government fiscal relationship was considered as the new era management and local government budget. The objectives of this study were (1) to identify factors affecting regional fiscal, regional economy, poverty ond food security and (2) to evaluate impact of fiscal decentralization policy on poverty and food security in West Java. The descriptive analysis and dynamic simultaneous equation models were used in this study, using pooled time series data of 1995-2005 and cross section data of 13 kabupatens estimated using the 2SLS method. The result of the study showed that the DAU was the source of 68% of regional income.The routine expenditures were the largest regional expenditures (77%). The policy of increasing agricultural development expenditures and wages affect poverty alleviation and increase food security in West Java. Key words: fiscal decentralization, economics growth, poverty allevation, food security